2006
DOI: 10.1007/s00535-006-1761-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits and stomach cancer in Mizoram, India

Abstract: Peculiar food habits in Mizoram might be associated with the high prevalence of stomach cancer in Mizoram along with other factors. H. pylori infection might increase the risk of stomach cancer, or it may play a role as a promoter of stomach cancer in Mizoram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 23 publications
4
45
0
Order By: Relevance
“…It was also reported that H. pylori was more common in diffuse type of cancer than intestinal type (86% vs 68%). Another study from Northern India reported the prevalence of H. pylori as high as 74% in controls as compared to 68% in gastric cancer cases (Phukan et al, 2006). A study from Mizoram reported higher rate of infection by H. pylori in stomach cancer patients (Parkin, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also reported that H. pylori was more common in diffuse type of cancer than intestinal type (86% vs 68%). Another study from Northern India reported the prevalence of H. pylori as high as 74% in controls as compared to 68% in gastric cancer cases (Phukan et al, 2006). A study from Mizoram reported higher rate of infection by H. pylori in stomach cancer patients (Parkin, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…A study from North India reported the prevalence of H. pylori infection to be 56.5% in gastric cancer patients (Ghoshal et al, 2008). A study from Mizoram reported higher rate of infection by H. pylori in stomach cancer patients (Phukan RK 2006 et al). Same study from Northern India reported the prevalence of H. pylori as high as 74% in controls as compared to 68% in gastric cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that consumption of alcohol, tobacco and different food habits are important risk factors of stomach cancer in addition to Helicobacter pylori infections (Correa, 1992;Russo et al, 2001;García-G et al, 2012). Earlier studies have shown that tobacco related habits are important risk factors for stomach cancer in Mizoram (Mahanta et al, 1998;Phukan et al, 2006). It was also shown that intake of tobacco in various traditional forms increases the risk of stomach cancer in Mizoram (Phukan et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…A unique pattern of tobacco consumption and dietary habits with high incidence of lung cancer was observed in Mizoram (Chaturvedi et al, 1998;Phukan et al, 2006;Malakar et al, 2014). Smoking of tobacco is undoubtly one of predominant risk factor for lung cancer (Tredaniel et al, 1994;Pisani et al, 2006;Sellappa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%